Financial accounting fundamentals - Wild, John J. (McGraw-Hill/Irwin, 2013)
Wild’s Financial Accounting Fundamentals responds to the market’s request for a low-cost, succinct book; a book that balances large and small businesses, and one that is contemporary, engaging, and accessible for today’s students. Its innovation is reflected in its extensive use of small business examples, the integration of new technology learning tools, superior end-of-chapter material, and a highly engaging, pedagogical design